ANALISIS HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MINAT DAN PRESTASI BELAJAR SISWA MADRASAH ALIYAH NEGERI 2 KOTA BIMA - Muhammad Iqbal (JUPE : Jurnal Pendidikan Mandala, 2022)
The impact and progress of science and technology (IPTEK) demands an increase in the quality of learning to support the process of achieving national education goals. To improve the quality and interest in learning, it is necessary to use media in the student learning process. the researcher used the quantitative method because the researcher wanted to know about the absence of a relationship between learning media and students' learning interests and achievements in economics class X Madrasah Aliyah Negeri 2 Kota Bima. The existence of a relationship between the use of instructional media and students' interest in learning can be seen from the values or achievement of student learning and this is also evidenced from the results of calculations using the product moment where the calculated value is greater than the r table value, namely 0.539 and 0.329 at a significant level of 5%. or 95% and a significant level of 1% or 99%, namely 0.539 and 0.424.